Wobble uridine tRNA modification: a new vulnerability of refractory melanoma. (2nd November 2018) - Rapino, Francesca; Close, Pierre
ABSTRACT: The enzymes catalysing the modification of the wobble uridine (U34 ) of tRNAs (U34 -enzymes) play an important role in tumor development. We have recently demonstrated that the U34 -enzymes are crucial in the survival of glycolytic melanoma cultures through a codon-specific regulation of HIF1α mRNA translation. Moreover, depletion of U34 -enzymes resensitizes resistant melanoma to targeted therapy. These results indicate that targeting U34 -enzymes represents a new therapeutic opportunity for melanoma patients.